2014
DOI: 10.2147/ott.s67921
|View full text |Cite
|
Sign up to set email alerts
|

Breast metastases of gastric signet-ring cell carcinoma: a report of two cases and review of the literature

Abstract: It is occasionally difficult to diagnose breast metastasis of gastric carcinoma because of its rarity. However, to appropriately treat patients with breast tumors without delay, it is important to distinguish metastatic cancer from primary breast cancer. We report two cases of breast metastasis of gastric carcinoma and review the literature. The first case was a 41-year-old female diagnosed with bilateral pelvic tumors who visited the outpatient clinic because of pain and enlargement of both breasts. Ultrasono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…According to current literature, the common metastasis site of stomach cancer (in ascending order) is the liver, peritoneum, lung and bone [ 34 , 35 ] while it is considerably rare to spread to the pancreas and skeletal muscle [ 36 , 37 ]. When compared to generic adenocarcinoma which often spreads to the liver and lung [ 38 ], signet-ring adenocarcinoma frequently metastasizes within the peritoneum, bone, ovaries and sometimes to the breast [ 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to current literature, the common metastasis site of stomach cancer (in ascending order) is the liver, peritoneum, lung and bone [ 34 , 35 ] while it is considerably rare to spread to the pancreas and skeletal muscle [ 36 , 37 ]. When compared to generic adenocarcinoma which often spreads to the liver and lung [ 38 ], signet-ring adenocarcinoma frequently metastasizes within the peritoneum, bone, ovaries and sometimes to the breast [ 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, studies of necropsies observed this uncommon event in patients with a breast cancer history ranging from 4% to 35%. Furthermore, 94% of these patients had other organs affected concomitantly 1 , 6 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The CK7 monoclonal antibody is present in tumors with glandular pattern, being observed at a maximum rate of 90% of breast cancers. It suggests breast cancer metastasis considering that only 50-64% of adenocarcinomas of the stomach present this molecule 8 , 10 , 11 . On the other hand, CK20 antibody presence favors the diagnoses of primary cancers from stomach, large bowel and pancreas 7 , 10 , 13 , 15 , 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premenopausal women are most commonly affected by the disease, and a previously reported average age at presentation is 47 years [40]. Examination of cases of metastatic gastric carcinoma to the breast reveals an increased percentage of patients affected by colorectal cancer, whereas the most common histological type is the signet-ring cell carcinoma, followed by mucinous carcinoma [41, 42]. Interestingly, signet-ring cell carcinoma is a unique subtype of mucin-producing adenocarcinomas, which can arise from the stomach, colon, and breast; thus, breast specimens obtained from gastric cancer patients should be carefully analyzed during pathology to differentiate between metastasis and a potential primary breast cancer [41, 43].…”
Section: Clinical Examplesmentioning
confidence: 99%